GAMES USED IN REHABILITATION AFTER STROKE: SCOPING REVIEW - Rita Pires Magalhães; Sara Rodrigues Barbeiro; Vanessa Taveira; Bruno Magalhães; Gustavo Ferreira (Associação Portuguesa dos Enfermeiros de Reabilitação, 2020)
Objectives: To explore the current state of scientific knowledge related to the use of games in the rehabilitation of individuals after stroke, with the objectives of mapping the games and identifying the areas of function rehabilitated. Method: Scoping review, based on Joanna Briggs Institute model. Search in MEDLINE®, CINAHL® and SPORTDiscus® databases. All types of scientific studies published in English, Spanish and Portuguese, without time limit, were considered. Results: In the 116 articles considered for analysis three major groupings of games were identified: Immersive / Non-Immersive Virtual Reality, Video Games and Traditional Games, which were associated with the rehabilitation of motor, proprioceptive, cognitive and cardiorespiratory functions. Conclusion: The use of games in rehabilitation has grown over the last few years. Games induce greater interactivity in intensive and repetitive training, adding more motivation and adherence to rehabilitation processes, which can be an important therapeutic resource.